Quality of Breast Cancer Information on the Internet by African Organizations: An Appraisal - Cynthia Pomaa Akuoko (International Journal of Breast Cancer)
Objective. The aim of this study was to appraise the quality of information on BC available at websites run by organizations in Africa. Methods. Three searches were conducted using Google search engine to generate a list of websites. The identified websites were assessed using European Commission (EC) quality criteria for health-related websites, which comprises different assessment areas including, completeness, transparency and honesty, authority, privacy and data protection, updating of information, accountability, and accessibility. Results. Thirteen (13) websites were included in the evaluation. Majority of the websites evaluated had low scores on the completeness and transparency of their websites. Scores on accessibility were however moderate and high for most of the websites. Breast cancer-specific organizations provided the highest quality information, particularly in terms of completeness. The overall lowest and highest quality scores were 9 and 43 out of 63, respectively, and 77% of the included websites scored less than 50% of the total quality score. Conclusion. This review has provided evidence of inadequate and inaccurate BC information provided by some cancer organizations in Africa. Considerable effort is required to make BC information on the Internet a valuable and up-to-date source for both professionals and patients.